Enhanced late sodium current underlies pro-arrhythmic intracellular sodium and calcium dysregulation in murine sodium channelopathy. (15th July 2018) - Rivaud, Mathilde R.; Baartscheer, Antonius; Verkerk, Arie O.; Beekman, Leander; Rajamani, Sridharan; Belardinelli, Luiz; Bezzina, Connie R.; Remme, Carol Ann
Abstract: Background: Long QT syndrome mutations in the SCN5A gene are associated with an enhanced late sodium current (INa, L ) which may lead to pro-arrhythmic action potential prolongation and intracellular calcium dysregulation. We here investigated the dynamic relation between INa, L, intracellular sodium ([Na + ]i ) and calcium ([Ca 2+ ]i ) homeostasis and pro-arrhythmic events in the setting of a SCN5A mutation. Methods and results: Wild-type (WT) and Scn5a 1798insD/+ (MUT) mice (age 3–5 months) carrying the murine homolog of the SCN5A- 1795insD mutation on two distinct genetic backgrounds (FVB/N and 129P2) were studied. [Na + ]i, [Ca 2+ ]i and Ca 2+ transient amplitude were significantly increased in 129P2-MUT myocytes as compared to WT, but not in FVB/N-MUT. Accordingly, INa, L wassignificantly more enhanced in 129P2-MUT than in FVB/N-MUT myocytes, consistent with a dose-dependent correlation. Quantitative RT-PCR analysis revealed intrinsic differences in mRNA expression levels of the sodium/potassium pump, the sodium/hydrogen exchanger, and sodium‑calcium exchanger between the two mouse strains. The rate of increase in [Na + ]i, [Ca 2+ ]i and Ca 2+ transient amplitude following the application of the Na + /K + -ATPase inhibitor ouabain was significantly greater in 129P2-MUT than in 129P2-WT myocytes and was normalized by the INa, L inhibitor ranolazine. Furthermore, ranolazine decreased the incidence of pro-arrhythmic calcium after-transients elicited in 129P2-MUT myocytes. Conclusions: In this study we established a causal link between the magnitude of INa, L, extent of Na + and Ca 2+ dysregulation, and incidence of pro-arrhythmic events in murine Scn5a 1798insD/+ myocytes. Furthermore, our findings provide mechanistic insight into the anti-arrhythmic potential of pharmacological inhibition of INa, L in patients with LQT3 syndrome. Highlights: Enhanced INa, L in LQT3 causes pro-arrhythmic increase in [Na + ]i and [Ca 2+ ]i. A dose-dependent relation exists between INa, L, [Na + ]i, [Ca 2+ ]i, and pro-arrhythmia. Genetic background determines INa, L, [Na + ]i, [Ca 2+ ]i, and arrhythmia severity. INa, L inhibition prevents pro-arrhythmic [Na + ]i and [Ca 2+ ]i dysregulation in LQT3.